Historiografi Islam Klasik - Kadril, Muhammad (Rihlah: Jurnal Sejarah dan Kebudayaan, 2021)
In this research was study that focused on Islam historiography in the classical era, that was very important to be discussed and analyzed because historiography was the parent of reconstructing history hence the role of historiography was very useful as a foundation for writing historical history. In this research there were several formulations of the issues raised by the researcher about: What were the topics discussed in the early period of Islamic historiography, as well as how the development of reading Islamic historiography. This type of research was a historical study hence it can analyze Islamic historiography in the classical period in depth hence it can know the various important things in the development of historiography starting from the initial themes of its writing to the process of its development. In the research process, it certainly used several approaches including the historical approach as the main approach in this research, the religious, and social approaches. The results of this study can reveal a variety of historiographies in the classical period besides the development of Islamic historiography writing to enter the figures who had succeeded in proclaiming many writings about Islamic historiography. Penelitian ini merupakan kajian yang berfokus pada historigrafi Islam pada masa klasik, hal ini sangatlah penting untuk dibahas dan dianalisis sebab historiografi merupakan induk dari merekonstruksi sejarah sehingga peranan historiografi sangatlah berguna sebagai peletak dasar penulisan sejarah. Pada tulisan ini terdapat beberapa rumusan masalah yang telah diajukan oleh penulis diantaranya : Apa topik pembahasan pada periode awal historiografi Islam, serta Bagaimana perkembangan penulisan historiografi Islam. Jenis kajian ini merupakan kajian sejarah sehingga dapat menganalisis historiografi Islam pada masa klasik secara mendalam serta dapat mengetahui berbagai hal penting dalam perkembangan historiografi mulai dari tema-tema awal penulisannya sampai pada proses perkembangannya. Pada proses penelitiannya tentu menggunakan beberapa pendekatan diantaranya pendekatan sejarahsebagai pendekatan utama dalam tulisan ini, pendekatan agama, serta sosial. Adapun hasil penelitian ini dapat mengungkap berbagai macam historiografi pada masa klasik selain itu adapula perkembangan penulisan historiografi Islam hingga masuk pada tokoh-tokoh yang telah berhasil memproklamir banyak tulisan tentang historiografi Islam.